(untitled) (Journal of Social Sciences Review, 2024)
In today’s world, people view companies as more than profit-driven organizations; there is an expectation from businesses to promote sustainable practices and improve the well-being of society. As a result, FMCG companies are rapidly embracing green branding initiatives to market environmentally sustainable products and encourage environmentally friendly consumption. This study aims to examine the effect of green branding, brand image, and green packaging on consumer green purchase intentions and the mediating effect of green brand image and environmental beliefs. Data from 285 survey participants were analyzed using Structural Equation Modeling (SEM). It is revealed that green packaging and branding affect consumer reaction positively, there is increasing green purchase intention, brand image effect, perceived value, eco-concern are mediators between awareness and action. These results are important for policymakers and firms looking to encourage sustainable consumer behavior through effective green marketing.